Homoplasmic m.591C >T variant in the mitochondrial MT-TF exhibits phenotypic heterogeneity: a family report - Shanshan Fan; Aiwen Wu; Feilong Wang; Jinliang Li (Egyptian Journal of Medical Human Genetics)
Abstract Background Mutations in mitochondrial transfer RNA (mt-tRNA) genes, a common source of mitochondrial DNA (mtDNA) mutations, are associated to diverse human diseases. These mutations are often heteroplasmic, leading to varied clinical symptoms. This study investigates the clinical and molecular features of a homoplasmic m.591C>T variant in the mitochondrially encoded tRNA phenylalanine gene (MT-TF), contributing to our understanding of mitochondrial diseases. Case presentation We describe a 2-year and 10-month-old boy with a homoplasmic m.591C>T variant in the MT-TF who presented with a unique combination of symptoms. He exhibited limb weakness, neck stiffness, delayed speech, short stature, and recurrent tetany, along with electrolyte imbalances, including hyponatremia, hypokalemia, and hypomagnesemia. Serial electroencephalogram (EEG) examinations were normal, suggesting that the limb weakness and tetany were due to hypomagnesemia. Treatment was effective, and the child recovered to a baseline state of health. His mother, who carried the same variant, suffered from uremia, easy fatigability, and poor endurance. hThe m.591C>T variant alters the conformation and stability of mt-tRNAPhe. Evolutionary analysis of m.591C > T variant showed that this position is relatively conserved. The m.591C > T variants were classified as pathogenic. Conclusions This case report highlights the significant clinical heterogeneity associated with the m.591C>T variant in the MT-TF even within the same family. It underscores the importance of integrating genetic, functional, and structural analyses to enhance our understanding, diagnosis, and management of mitochondrial diseases with individualized presentations.